Challenges of Digital Services: Case Study of Citizenship Administrative Services in Bekasi City, Indonesia - Budiarjo, Budiarjo (Iapa Proceedings Conference, 2024)
Towards world class bureaucracy, digitalization of government administration is one of the big agendas implemented by the Indonesian government. In the field of public services, manual services have been shifted and replaced with online services which are considered faster and cheaper. However, online services have challenges that are not easy. Until early 2023, 63.5 million Indonesians were not be connected to the internet. In addition, there are 33% of citizens who do not have the smartphone needed to access online services. This study will aim to describe various problems and challenges in the digitalization of public services and formulate policy recommendations needed to overcome them, especially in the case of citizenship administrative services in Bekasi City.